Characterization of Hop Extracts and Extracts from some Selected Nigerian Plants by GC-MS and Brewing Qualities Analyses - Okafor, Vincent Nwalieji; Anyalebechi, Regina Igwe; Okafor, Ugochukwu Wilson (IJRDO-Journal of Applied Science, 2016)
Humuluslupulus L (hop) plants and four selected Nigerian plants namely Azadirachtaindica(neem), Garcinia kola (bitter cola), Gongronemalatifolium(heckel) and Vernoniaamygdalina (bitter leaf) as substitutes for hops in beer brewing were characterized in terms ofmethanolic and aqueousextracts using Gas Chromatography - Mass Spectrometer (GC-MS-Q2010 plus, Shimadzu, Japan). The brewing qualities (isoalpha acid and essential oil contents)of the extracts were investigated using standard methods. Statistical analysis was carried out on the result of brewing qualities tests by the application of one way analysis of variance (ANOVA). The GCMS results showed that these plants contained metabolites comparable to those of hops, although some metabolites[dehydro-cohumulunic acid; 4,4-dimethyl-2-buten-4-olide; 1,2-dimethylcyclopropane carboxylic acid; lupulone; 2,5-dimethyl-2-hexanol; 4,4,5,5-tetramethylbicyclo hexyl-6-ene-2,3-dione; octadecanoic acid, oxiranyl methyl ester and 1,2- benzenedicarboxylic, bis(-2-ethyl hexyl) ester] present in hops were absent in the Nigerian plants. Isomerized hop, hop leaf, G. kola and V. amygdalinacontained a total number of 14, 11, 12 and 9 metabolites respectively while A. indcaand G. latifolium each contained a total number of 10 metabolites.The brewing qualities investigated showed that iso-alpha acid ranged from 8.78-12.53ppm and essential oil ranged between 5.44-10.12g/100g. This study revealed that the brewing qualities of all the extracts did not differ significantly. Hence, extracts from tested Nigerian plants present potential substitutes for hops in the Nigerian brewing industry without significant alteration to the brewing qualities. Consequently, academic activity in the area of mixtures/blends of extract of plant species which mimic hop taste is strongly recommended.